PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN ARTICULATE STORYLINE 3 UNTUK MELATIH KEMAMPUAN PEMAHAMAN KONSEPTUAL PESERTA DIDIK KELAS VII - Salam, Anisa Zahra Aprilia; Setialesmana, Depi; Herawati, Linda (De Fermat : Jurnal Pendidikan Matematika, 2026)
This study focuses on developing learning media assisted by Articulate Storyline 3 to train the conceptual understanding skills of seventh-grade students. The research used an R&D method with the ADDIE model by Lee and Owens. The study involved seventh-grade students of SMP Negeri 3 Kota Tasikmalaya and expert validators as research subjects. The research began with the analysis stage to identify the students’ needs. The results of the analysis were then used in the design stage to prepare the entire learning media plan, which was developed based on indicators of conceptual understanding skills. In the development stage, the design was integrated into Articulate Storyline 3 to produce an application. The learning media application was validated by experts and received a “Very Feasible” rating for use. Next, the implementation stage involved small-scale and large-scale trials with seventh-grade students at SMP Negeri 3 Kota Tasikmalaya to determine the effectiveness of the learning media in training conceptual understanding skills. Finally, the evaluation stage processed all data obtained from the small-scale and large-scale trials. The results showed that the development of learning media assisted by Articulate Storyline 3 was conducted systematically and underwent expert validation. The media was also found to be effective in training conceptual understanding skills, with the conceptual understanding test results rated “Excellent” and student responses after using the media rated “Very Feasible.”